A complex pathway for 3′ processing of the yeast U3 snoRNA - Kufel, Joanna (Oxford University Press, 2003)
Mature U3 snoRNA in yeast is generated from the 3′-extended precursors by endonucleolytic cleavage followed by exonucleolytic trimming. These precursors terminate in poly(U) tracts and are normally stabilised by binding of the yeast La homologue, Lhp1p. We report that normal 3′ processing of U3 requires the nuclear Lsm proteins. On depletion of any of the five essential proteins, Lsm2–5p or Lsm8p, the normal 3′-extended precursors to the U3 snoRNA were lost. Truncated fragments of both mature and pre-U3 accumulated in the Lsm-depleted strains, consistent with substantial RNA degradation. Pre-U3 species were co-precipitated with TAP-tagged Lsm3p, but the association with spliced pre-U3 was lost in strains lacking Lhp1p. The association of Lhp1p with pre-U3 was also reduced on depletion of Lsm3p or Lsm5p, indicating that binding of Lhp1p and the Lsm proteins is interdependent. In contrast, a tagged Sm-protein detectably co-precipitated spliced pre-U3 species only in strains lacking Lhp1p. We propose that the Lsm2–8p complex functions as a chaperone in conjunction with Lhp1p to stabilise pre-U3 RNA species during 3′ processing. The Sm complex may function as a back-up to stabilise 3′ ends that are not protected by Lhp1p.